HR without people? : industrial evolution in the age of automation, AI, and machine learning - Wheeler, Anthony R.; Buckley, M. Ronald (Emerald Publishing Limited, 2021)
As artificial intelligence and machine learning practices grow, entire industries and jobs could become more automated or cease to exist altogether. HR Without People? traces provocative and challenging timelines for future developments in ten, thirty and fifty years' time, to interrogate how modern HR practices need to respond to far reaching technological and industrial change. Focusing on the role these technologies are playing in changing the HR profession and how they could and should develop industry practices in the future, HR experts Anthony R. Wheeler and M. Ronald Buckley explore how this profession has a vital role in responding to these changes and how it can adapt to meet the new challenges faced by both employers and employees. Examining key issues such as the effects of big data and algorithms ongoing role in influencing recruiting and selection, the changes in virtual technology that will alter training, and how the role of government will expand to address the needs of citizens affected by the rate of change in workforce displacement, HR Without People? is a stimulating and confrontational challenge to conventional thinking on this people-centric profession's role in the future of work.
Includes index.
Keywords: Personnel management -- Forecasting.; Automation -- Human factors.; Personnel management -- Technological innovations.; Business & Economics -- Human Resources & Personnel Management.; Personnel & human resources management.; elektronické knihy; electronic books